Homo Sacer: Ahmadiyya and Its Minority Citizenship (A Case Study of Ahmadiyya Community in Tasikmalaya) - Ach. Fatayillah Mursyidi; Zainal Abidin Bagir; Samsul Maarif (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2020)
Citizenship is among the notions mostly contested after the collapse of a long-standing authoritarian regime in 1998. The reform era – after 1998 - radically transformed Indonesia into a democratic country and brought many other issues including minority issues into the forefront. Unlike other countries that draw their citizenship on a clear formula between religious and secular paradigm, Indonesia, due to ambivalence of its religion-state relation, exhibits fuzzy color of citizenship that leaves space for majority domination over the minority. In consequence, the status of Ahmadiyya for instance, as one of an Islamic minority group, is publicly questioned both politically and theologically. Capitalized by two Indonesian prominent scholars, Burhani (2014) and Sudibyo (2019), I conducted approximately one-month field research in Tasikmalaya and found that what has been experienced by Ahmadiyya resembles Homo Sacer in a sense that while recognised legally through constitutional laws, those who violate their rights are immune to legal charges. This leads to nothing but emboldening the latter to persistently minoritise the former in any possible ways.